Problematika Penerapan Sistem Nizham al-Wihdah pada Pembelajaran Bahasa Arab di SMP IT Najib Bariq Bandung - Fu’adah, Silvia Tsamrotul; Kosim, Nanang (STAINI Press, 2024)
Arabic language learning has a different learning system in the learning process. There are two divisions in the Arabic language learning system, namely Nizham Al Wihdah which is also called an integrated system which means that learning Arabic is a language that is a closely related unit and is not presented in a separate form. Second, Nizham al Furu', namely the theory of branches or separation of Arabic language material. The aim of this research is to find out the problems and solutions in implementing the Nizham Al Wihdah system in Arabic language learning at SMP IT Najib Bariq Bandung. This research method is qualitative case study research based on data collection: in-depth interviews, documentation, and participatory observation. The researcher concluded that the results of this research were problems that occurred due to inadequate allocation of time and facilities and the advice needed was teachers who were appropriate in their field and used the language environment as a solution to this problem